2016
DOI: 10.2147/ceor.s124023
|View full text |Cite
|
Sign up to set email alerts
|

Economic report on the cost of dengue fever in Vietnam: case of a provincial hospital

Abstract: BackgroundDengue is a mosquito-borne viral illness with the world’s fastest rate of infection. In 2014, Vietnam had recorded 43,000 cases in 53 provinces, with 28 deaths.Materials and methodsA 6-month cross-sectional study was conducted from September 2015 to March 2016 at Cu Chi General Hospital. Cost of illness in this study was estimated under the incidence-based approach from the societal perspective.ResultsThe average cost per case was US$139.3±$61.7. The average cost per child was higher than per adult, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Compared to previous studies, participants in this study were older (33.9 ± 14.3) (the reported average age of patients in studies conducted nationally in 2011 and at Cu Chi General Hospital in 2016, was 24 ± 7.2 years and 23.2 ± 13.3 years, respectively) [ 14 , 15 ]. This indicated that working adults are still most vulnerable to the virus, albeit more so in the higher age group.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Compared to previous studies, participants in this study were older (33.9 ± 14.3) (the reported average age of patients in studies conducted nationally in 2011 and at Cu Chi General Hospital in 2016, was 24 ± 7.2 years and 23.2 ± 13.3 years, respectively) [ 14 , 15 ]. This indicated that working adults are still most vulnerable to the virus, albeit more so in the higher age group.…”
Section: Discussionmentioning
confidence: 56%
“…The epidemic was mostly concentrated in urban areas, such as Hanoi and Ho Chi Minh city, resulting in an overload on the hospital system in Vietnam, particularly in central hospitals with infectious departments. Albeit a prevalent disease, only limited studies have explored the effects of DF on the quality of life of patients, as well as the financial burden that is suffered by those who are infected in Vietnam [ 14 , 15 , 16 ]. This data is critical in supporting the decision-making processes of clinical practitioners and will partly contribute to further economic evaluations for DF prevention, cure, and control interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We identified seven studies that reported costs related to hospitalized dengue cases in Vietnam. The reported average cost per case varied between US$115 and US$278 in 2016 prices ( Table 1 ) 28 , 29 , 30 , 31 , 32 , 33 , 34 . The average total cost per case was relatively consistent across the different studies, with the exception of the estimate from Tam et al .…”
Section: The Estimates Of the Economic Burden Of Dengue Illness In VImentioning
confidence: 99%
“… 71.82 26.17 19.62 117.61 Pham et al . [28] Patients from one hospital in a suburban area of Ho Chi Minh City were interviewed. Direct medical costs were also collected from the hospital’s electronic database.…”
Section: The Estimates Of the Economic Burden Of Dengue Illness In VImentioning
confidence: 99%
See 1 more Smart Citation